Use of Gadgets With Preschool Developmental Disorders; Study Literature Review - Yuliani, Eva (Journal of Health Education and Literacy, 2020)
Preschool children experience rapid physical, motor, intellectual, language and social development processes. Growth and development during the preschool period is a very influential basic stage and forms the basis for further development. One of the factors or stimuli that can affect children's development is the child's habit of playing gadgets. The aim is to find out more about the Screen Time of Gadget Usage with developmental disorders of pre-school children. Method: In this literature review, it was obtained from the Google Schoolar database, journals selected from the last 5 years 31 May 2015 to 31 July 2020 which consisted of 4 research results from 4 different journals. The keywords used are "Gadget Usage, preschool, and Development Disorders". Result: Screen time using gadgets affects developmental disorders of pre-school children. The conclusions of the 4 journals reviewed show that Gadget Use affects the developmental disorders of pre-school children.